HIF Prolyl-4-hydroxylase Interacting Proteins: Consequences for Drug Targeting - Wenger, Roland H.; Camenisch, Gieri; Stiehl, Daniel P.; Katschinski, Dorthe M. (Current Pharmaceutical Design, 2009)
Protein stability of hypoxia-inducible factor (HIF) α subunits is regulated by the oxygen-sensing prolyl-4- hydroxylase domain (PHD) enzymes. Under oxygen-limited conditions, HIFα subunits are stabilized and form active HIF transcription factors that induce a large number of genes involved in adaptation to hypoxic conditions with physiological implications for erythropoiesis, angiogenesis, cardiovascular function and cellular metabolism. Oxygen-sensing is regulated by the co-substrate-dependent activity and hypoxia-inducible abundance of the PHD enzymes which trigger HIFα stability even under low oxygen conditions. Because HIFα itself is notoriously reluctant to the development of antagonists, an increase in PHD activity would offer an interesting alternative to the development of drugs that interfere specifically with the HIF signalling pathway. Interestingly, among the recently discovered PHD interacting proteins were not only novel downstream targets but also upstream regulators of PHDs. Their PHD isoform-specific interaction offers the possibility to target distinct PHD isoforms and their non-identical downstream signalling pathways. This review summarizes our current knowledge on PHD interacting proteins, including upstream regulators, chaperonins, scaffolding proteins, and novel downstream transcription factors.
Keywords: Asparaginyl hydroxylase